Establishment and Validation of a New Co-Culture for the Evaluation of the Permeability through the Blood-Brain Barrier in Patients with Glioblastoma - Bárbara Sánchez-Dengra; Elena García-Montoya; Isabel González-Álvarez; Marival Bermejo; Marta González-Álvarez (MDPI AG, 2023)
Currently, the mechanisms involved in drug access to the central nervous system (CNS) are not completely elucidated, and research efforts to understand the behaviour of the therapeutic agents to access the blood-brain barrier continue with the utmost importance. The aim of this work was the creation and validation of a new in vitro model capable of predicting the in vivo permeability across the blood-brain barrier in the presence of glioblastoma. The selected in vitro method was a cell co-culture model of epithelial cell lines (MDCK and MDCK-MDR1) with a glioblastoma cell line (U87-MG). Several drugs were tested (letrozole, gemcitabine, methotrexate and ganciclovir). Comparison of the proposed in vitro model, MDCK and MDCK-MDR1 co-cultured with U87-MG, and in vivo studies showed a great predictability for each cell line, with R2 values of 0.8917 and 0.8296, respectively. Therefore, both cells lines (MDCK and MDCK-MDR1) are valid for predicting the access of drugs to the CNS in the presence of glioblastoma.